Comparison of the Effects of Environmental Parameters on the Growth Variability of Vibrio parahaemolyticus Coupled with Strain Sources and Genotypes Analyses - Liu, Bingxuan; Liu, Haiquan; Pan, Yingjie; Xie, Jing; Zhao, Yong (Frontiers in Microbiology, 2016)
Abstract Microbial growth variability plays an important role on food safety risk assessment. In this study, the growth kinetic characteristics corresponding to maximum specific growth rate (μmax) of 50 V. parahaemolyticus isolates from different sources and genotypes were evaluated at different temperatures (10 °C, 20 °C, 30 °C, 37 °C) and salinity (0.5%, 3%, 5%, 7%, 9%) using the automated turbidimetric system Bioscreen C. The results demonstrated that strain growth variability increased as the growth conditions became more stressful both in terms of temperature and salinity. The coefficient of variation (CV) of μmax for temperature was larger than that for salinity, indicating that the impact of temperature on strain growth variability was greater than that of salinity. The strains isolated from freshwater aquatic products had more conspicuous growth variations than those from seawater. Moreover, the strains with tlh+/tdh+/trh- exhibited higher growth variability than tlh+/tdh-/trh- or tlh+/tdh-/trh+, revealing that gene heterogeneity might have possible relations with the growth variability. This research illustrates that the growth environments, strain sources as well as genotypes have impacts on strain growth variability of V. parahaemolyticus, which can be helpful for incorporating strain variability in predictive microbiology and microbial risk assessment.